Increasing the Strength of the Land Transportation B2B Logistics Business with Cloud-Based Applications in Jabodetabek in the Covid-19 Era - Yogi Ashari; Tri Mulyani Setyowati; Erni Pratiwi Perwitasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is a quantitative study that analyzed the impact of IT/Cloud-Based Application on various variables in the logistics business in the JABODETABEK area. The data was collected from a survey of logistics companies and service users and analyzed using Structural Equation Modelling (SEM) based on Partial Least Square (PLS). The results showed that the implementation of IT/Cloud-Based Application had a positive and significant impact on market positioning but did not have a significant impact on product innovation, business resilience, and revenue improvement. The study suggests that companies that can adapt to market changes and use IT/Cloud-Based Application will have a better market positioning and competitiveness, especially in light of the changes brought about by the COVID-19 crisis.